Surgical Atlas of Cleft Palate and Palatal Fistulae - Fayyaz, Ghulam Qadir; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
Globally there is a burden of approximately 1, 60,000 new cases of cleft lip and palate every year, yet there is no single comprehensive source on this problem. This surgical atlas fills the gap in the knowledge of appropriately handling cleft lip and palate cases. This pictorial resource has been compiled and edited by an expert who operates one of the highest cleft lip and palate correction programs in the world and has performed more than 34,000 surgeries, restoring function to numerous patients across the globe. It covers all variants and types of cleft lip and palate defects, including both primary cases as well as in previously operated cases. It starts with an in-depth elaboration on anatomy, physiology, and pathology of the (normal) palate and cleft palate, moving towards, classification and identification of defects with the help of clear flow charts and simple algorithms enabling better diagnosis and decision making. With over 1500 high definition images and hand-drawn sketches, this atlas provides a detailed description of diagnosis, problems and the management of each type of defect. The underlying objective of such surgeries is to best restore the good function of the palate and enable better speech production, which is highlighted amply in each chapter. This atlas is a valuable resource for all plastic surgeons, paediatric surgeons, maxillofacial surgeons, ENT surgeons and other medical professionals involved in cleft lip and palate defect surgeries.
Anatomy and Patho-Phsyiology of Cleft Palate -- Classification of Cleft Palate -- Management of Cleft Palate Patient -- Objectives of Palate Repair -- Different Techniques of Palate Repair -- New Techniques and Innovations -- Post Operative Management of Cleft Palate Repair -- Complications of Cleft Palate Repair -- Pakistan Comprehensive Fistula Classification -- Management of Midline Palatal Fistula -- Management of Lateral Palatal Fistula -- Management of Subtotal Fistulae -- Management of Multiple Fistulae & FAR -- Dehiscence/Almost Total Loss of Palatal Tissue -- Difficult to Repair Secondary Palate Patients -- Speech Therapy -- Orthognathic Surgery after Cleft Palate Repair.
Keywords: Otorhinolaryngology; Surgery; Otorhinolaryngology; Surgery; Cleft Lip -- surgery; Cleft Palate -- surgery; Palate -- abnormalities